Street art and graffiti in former communist Albania from 2010 to 2022 - Muharremi, Ilir Hivzi; Krasniqi, Albana (Street Art & Urban Creativity, 2022)
This paper deals with graffiti in the streets of Albania, a former communist state which in the time of communism had every modern motif banned, except the art of propaganda that was under the service of the party. Graffiti on the walls of buildings in different cities of Albania since 2010 has social, political, economic, psychological, social, and personal motives. It shows the development of murals, the freedom of expression of artists, and positive propaganda through this art. In Albania, artists are now free to express all their artistic ideas, and graffiti is used as public art which reflects any current events occurring. Color is the main element that distinguishes mural artists, as well as motive and figuration.